ANALISIS PENGARUH TOTAL PANJANG ELEKTRODA BATANG TERHADAP PENTANAHAN DENGAN MENGGUNAKAN METODE WENNER DAN DRIVEN ROD - Zaldi, Farham Muhammad; Kali, Agustinus; Martdiansyah, Martdiansyah; Khairunnisa, Khairunnisa (Foristek, 2024)
This research discusses the influence of electrode depth, number of electrodes and the influence of the Wenner and Driven Rod methods on reducing the value of grounding resistance. The ground electrode is a conductor that is embedded in the earth and makes direct contact with the earth, where the ground electrode is used as a grounding system tool if a disturbance occurs in the electric power system. The method used is a quantitative method, namely a method that uses research data resulting from direct observation, where the data is produced in the form of numbers that will be analyzed. The results obtained were that the influence of the depth of the grounding electrode was not effective enough, because the soil used had moisture that was not much different between a depth of 1 meter and 2 meters. The effect of the number of grounding electrodes used is very effective because the resistance value obtained is lower. The effect of the Wenner method produces a greater reduction compared to the Driven Rod method, Wenner experienced a decrease of 52.4 ohms on dry soil and 33.4 ohms on wet soil and Driven Rod experienced a decrease in resistance value of 49.7 ohms on dry soil and 29.23 ohms on wet ground. The conclusion obtained is that the total electrodes used are more influential in reducing the grounding resistance value than the length of the depth of the implanted electrodes and the Wenner method is better in reducing the grounding resistance value than the Driven Rod method.